2(x-6)=3(x-+2)

Simple and best practice solution for 2(x-6)=3(x-+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-6)=3(x-+2) equation:



2(x-6)=3(x-+2)
We move all terms to the left:
2(x-6)-(3(x-+2))=0
We add all the numbers together, and all the variables
2(x-6)-(3(+x))=0
We multiply parentheses
2x-(3(+x))-12=0
We calculate terms in parentheses: -(3(+x)), so:
3(+x)
We multiply parentheses
3x
Back to the equation:
-(3x)
We add all the numbers together, and all the variables
-1x-12=0
We move all terms containing x to the left, all other terms to the right
-x=12
x=12/-1
x=-12

See similar equations:

| 3y+(3+-1y)=5 | | 48x+46-18x= | | .67x^2+35=87 | | 81=-3(-4a-7) | | y7=13 | | -4(3x+5)=5x-7 | | 3m-20=m+40 | | 2(-2x+6)=7x+1 | | x2+6x+9=1 | | 64=6w+16+8w | | -0,8x^2+9x+1=15 | | 8.6=1.8y-5.4 | | 0=21x2-14x+7 | | 10+1/2x=1 | | 3/2x-1/2=3/5x-19 | | 64=6w+8+2w | | 2w+8=34 | | x+3^2=49 | | 10/3=20/i | | 3x-8-5x=-7+9x+2 | | 2x-1=x+3x= | | 41+7w-45=9w-48 | | (7t2)(3t+1)=3(13t) | | 49=2v+9 | | 60(t+1)=70t | | 2-x+8=3(x)+6 | | 11x+x^2-30=0 | | -5x+32=5(-x+7)-3 | | -4-1/8x=-21/8x | | x^+3/4x+1/8=0 | | 2s+7s-5=3-2s | | 2+7-6n-4=-2n+5 |

Equations solver categories